The study of Indonesian verbs berkata, bersabda, and berfirman - Majid Wajdi; Ikhsanudin Ikhsanudin; Md Kamrul Hasan; Fatema Sharmin (Politeknik Negeri Bali, 2020)
This research aims to analyze the existence of the Indonesian verbs “berkata”, “bersabda”, and “berfirman” (to say, to state). The method of document study was executed to provide the data, namely the translation of the Holy Quran (2004). Although it is unfair to compare the language of Indonesia and the language of Java from a speech level point of view, this paper is simply meant to trace how the words of the language of Indonesia show its speech levels in its own way. The Indonesian verbs “berfirman”, “bersabda”, and “berkata” are used to describe the activity of ‘saying’ or ‘speaking’ of God (berfirman), the Prophet Muhammad (bersabda), and people in common (berkata). It is concluded here that there are speech levels in the language of Indonesia, but they are not to compare with the speech levels like in the language of Java, Bali, Madura, Sunda, and or Sasak of Lombok.